Analisis Keterampilan Metakognisi Siswa SMP Negeri di Kota Malang Berdasarkan Kemampuan Awal, Tingkat Kelas, dan Jenis Kelamin - Cut Nurmaliah (Universitas Syiah Kuala, 2009)
The purpose of this research is to analyze skills of metacognition students of 24 State SMP in Malang City base on pre knowledge, class level, and sex category . The instruments used in this study were meta-cognition of inventory junior and rating scale of meta-cognition skill. Anava Factorial is continued with further test by differentiate test with LSD (Least Significant Different) are used in analyzing the data. The result of the study showed female students are more active than male students in questioning, answering questions and presenting the result of observation. Female students are superior in meta-cognition than male students. For students in class 8, the metacognition are lower than those who are in class 7 and class 9. Based on pre knowledge, class level, and sex show meta-cognition in the level of OK